Central retinal artery occlusion or retinal stroke: a neurosonologist’s perspective - Taroza, Saulius; Jatužis, Dalius; Matijošaitis, Vaidas; Raugelė, Saulius; Valaikienė, Jurgita (Frontiers in Neurology, 2024)
In central retinal artery occlusion (CRAO) or retinal stroke, which is usually a vision-threatening condition, timely diagnosis is imperative to improve the chances of retinal preservation and to establish adequate secondary prevention measures. Even though retinal strokes have been traditionally assigned to the field of ophthalmology, while considering a reperfusion therapy as an only way to avoid permanent vision loss, we suggest prompt evaluation of CRAO causes (primarily related to cardiovascular risk factors) performed by a well-organized interdisciplinary team (ophthalmologist and neurologist) in a neurovascular center with stroke expertise. Therefore, the most suitable adjunct method for rapidly diagnosing non-arteritic CRAO could be target transorbital ultrasound, performed by an experienced neurologist/neurosonologist working in the stroke unit. Consequently, after an ophthalmological assessment, a final decision on thrombolytic therapy could be made. We accept that further research is obviously needed whether transorbital ultrasound could replace ophthalmological investigation in case of suspected acute retinal stroke. We assert that retinal stroke requires interdisciplinary treatment in cooperation with neurologists and ophthalmologists, with an additive value for each to achieve the best results for the patient.